Avaliação da resistência flexural de resinas acrílicas polimerizadas por micro-ondas: influência do tempo de prensagem e armazenagem pós-polimerização - Dessete, Lilian Perin [UNESP] (2012)
Fractures of acrylic resins for denture bases are common problems in daily dental surgeon. These fractures are initiated with the formation of cracks and propagate through areas of high concentrations of stress. The masticatory forces focus on artificial teeth reflecting different magnitudes in the areas of the bases, which in turn result in the most affected areas of strength. The flexural strength of the polymerized material must necessarily be within values compatible with the standards established in the rules so that if the device ensures longevity. Based on these considerations, the purpose of this study was to assess the importance of pressing time and storage of post-curing on the flexural strength of acrylic resins polymerized by microwave energy Cryl Wave ® Wave ® and Vipi. 60 bodies were made of the test piece for each acrylic resin studied, standardized according to Spec # 12 of the American Dental Association (65 x 10 x 2.5 mm). The finish was done in lathe and polished with sandpaper following the sequence: 200, 500, 600, 800 end 1200 . The body-of-evidence were divided into 12 groups (n = 10) distinguished: Group I - Vipi Wave - Pressing conventional Group II - Vipi Wave - Pressing conventional storage + distilled water 24 hours; Group III - Vipi Wave - Pressing conventional distilled water storage + 30 days; Group IV - Vipi Wave - Pressing 24 hours; Group V - Vipi Wave - Pressing 24 hours + 24 hours storage distilled water; Group VI - Vipi Wave - Pressing storage 30 days 24 hours + distilled water; Group VII - Wave Cryl - Pressing conventional, Group VIII - Wave Cryl - Pressing conventional storage + distilled water 24 hours; Group IX - Wave Cryl - Pressing conventional storage + distilled water 30 days; Group X - Wave Cryl - Pressing 24 hours; Group XI - Wave Cryl - Pressing 24 hours + 24 hours storage distilled...